Research on the hydraulic support top beam based on dynamic load bearing - Cao, Lianmin; Jin, Xin; Qin, Jianli; Zhang, Xiaowei; Gao, Lili (Frontiers in Earth Science, 2023)
Aiming at the problem of structural damage of top beam and column in the actual bearing process of top coal caving hydraulic support caused by uneven roof pressure in the process of fully mechanized caving mining in thick coal seam coal mine, this paper analyzes the dynamic bearing performance of ZF20000/26/48 top coal caving hydraulic support based on the working conditions given by the 101 working face of Shaanxi Zheng-tong Coal Mine. According to the simulation analysis results, the support top beam is optimized and improved, and the specific top beam optimization parameters are given by using genetic algorithm. The bearing capacity of the support before and after optimization, results showed: Under the same loading conditions, the maximum stress of the optimized support is reduced by 22.28MPa, and the stress of the top beam is more uniform, and the maximum stress is reduced by 24.53MPa, The purpose of optimization design is achieved, and the bearing performance of hydraulic support is improved.